Analisis Penerapan Model Pembelajaran Problem Based Learning Pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Putri Mas Intan Silalahi; Demmina Ginting; Shofyani Salasa; Indah Mutia; Yusnadi Yusnadi; Anita Yus (Jurnal Tematik, 2025)
The aim of this study is to analyze the implementation of the Problem Based Learning (PBL) Model in Integrated Thematic Learning in Elementary Schools. The main focus of this study is to analyze the suitability of the syntax in the application of the problem-based learning model in integrated thematic learning in elementary schools. Thematic learning in elementary schools is designed to improve and enrich the quality of education in a more enjoyable and meaningful way for students. The problem-based learning model is a learning model that can encourage students to actively participate in solving problems through a series of scientific method activities, so that the knowledge gained can be meaningful. The method used is a qualitative approach with descriptive research type. Data sources were obtained through primary and secondary data, with data collection techniques including observation, interviews, and documentation. The research results indicate that the implementation of the PBL model has not been carried out well and effectively in Grade VI at Langkat State Elementary School. There were inconsistencies in the PBL model's syntax or steps at certain stages, such as the teacher not clearly communicating the learning objectives, insufficiently encouraging student engagement in problem-solving, and not providing reflection at the end of the lesson. Furthermore, the students were less enthusiastic and focused, resulting in the learning objectives not being optimally achieved.